Teachers as users of ICT from the student perspective in higher education flipped classroom classes - Sointu, Erkko T.; Valtonen, Teemu; Hirsto, Laura; Kankaanpää, Jenni; Saarelainen, Markku; Mäkitalo, Kati; Smits, Anneke; Manninen, Jyri (Seminar.net, 2019)
<iframe style="width: 100%; height: 100%; position: absolute; top: 0; left: 0;" src="https://film.oslomet.no/53047809.ihtml/player.html?token=aa321d7127119608424498d42e9423e5&source=embed&photo%5fid=52172269" frameborder="0" scrolling="no" allowfullscreen="1"> The use of information and communication technology (ICT) is important in today’s higher education. ICT has a central role in the skill set students are expected to master during their studies. The fast development of technology poses both possibilities and challenges for teachers. This paper is part of a larger project aimed at implementing the flipped classroom (FC) model and supporting ICT integration in higher education. In this project, teachers receive systematic support for implementing the FC model. The aim of this paper is to investigate how students assess their teachers’ knowledge of pedagogy, content and technology before and after a course using the FC model. In total, 317 students responded to the pre-post-test surveys. The data were analyzed as a single group and separately for students in different year groups. Results indicate that there are statistically significant differences between the results of the pre- and post-tests. Students assess their teachers content-specific pedagogical skills and technological pedagogical skills in teaching their subject higher after the FC courses. Students also perceived their teachers as having more positive attitudes to using technology in teaching. It was found that the difference was more apparent in second-year and higher students. Students perceived FC positively in general.